Unoccupied titanium 3d states due to subcluster formation in stoichiometric TiO2 nanoparticles. Issue 17 (11th June 2015) - Auvinen, Sami; Lahti, Matti; Alatalo, Matti
<x xml:space="preserve">Abstract</x> The source of unoccupied Ti 3d states in the case of stoichiometric anatase structured (TiO2)n clusters has been investigated using ab initio methods. These unoccupied gap states appear for example in the case of a stoichiometric (TiO2)38 cluster. We show that the origin of these gap states is related to effective subcluster formation which gives rise to empty defect‐like gap states, when these states are split off from conduction band. © 2015 Wiley Periodicals, Inc.